2016
DOI: 10.1016/j.vetpar.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

First report of parasitism by Hexametra boddaertii (Nematoda: Ascaridae) in Oxyrhopus guibei (Serpentes: Colubridae)

Abstract: The current study summarizes the postmortem examination of a specimen of Oxyrhopus guibei (Serpentes, Colubridae) collected in Iguazu National Park (Argentina), and found deceased a week following arrival to the serpentarium of the National Institute of Tropical Medicine (Argentina). Although the snake appeared to be in good health, a necropsy performed following its death identified the presence of a large number of roundworms in the coelomic cavity, with indications of peritonitis and serosal adherence. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Coinciding with Melgarejo-Giménez (2006), we also found that rhabdiasid nematodes are the most frequent among them. Furthermore, we identified Erythrolamprus aesculapii as a new host for Hexametra boddaertii, highlighting the possibility of zoonotic transmission of this helminth from snake to human (Peichoto et al, 2016). In fact, this nematode genus was previously reported in cases of ocular and visceral larva migrans in humans (Goodart et al, 1985; Bowman, 1987).…”
Section: Discussionmentioning
confidence: 93%
“…Coinciding with Melgarejo-Giménez (2006), we also found that rhabdiasid nematodes are the most frequent among them. Furthermore, we identified Erythrolamprus aesculapii as a new host for Hexametra boddaertii, highlighting the possibility of zoonotic transmission of this helminth from snake to human (Peichoto et al, 2016). In fact, this nematode genus was previously reported in cases of ocular and visceral larva migrans in humans (Goodart et al, 1985; Bowman, 1987).…”
Section: Discussionmentioning
confidence: 93%
“…We also retrieve sequences from Platyhelminthes, Nematoda, and Apicomplexa. All three phyla are known gut community members ( De Chambrier & De Chambrier, 2010 ; Molnár et al, 2012 ; Peichoto et al, 2016 ). In addition to the phyla common to all four samples, we find taxa specific to individual hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the common occurrence of Hexametra in lizards and snakes, there are few reports of associated mortality (Jacobson, 2007). An infection of Hexametra boddaertii (Baird, 1860) was found in a wild-caught snake in Argentina; the snake died after a few days despite being in apparent good health (Peichoto et al ., 2016). Over 100 nematodes were collected from the coelomic cavity (smaller worms) and the intestinal tract (larger worms); initial fecal examination had shown a heavy infection with ascaridoids but attempts to de-worm the snake were unsuccessful (Peichoto et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%